Commodification of Reporting on Positive Palm Oil Issues in Local Indonesian Media - sri astuty; Yuwanto Yuwanto; Laila Kholid Alfirdaus; Bachruddin Ali Akhmad (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study is based on the existence of local media that specifically addresses environmental issues with positive news about oil palm plantations. This is marked by the existence of a special news column that examines the various potentials and benefits of palm oil. This research aims to analyze the content of positive palm oil issues in local media and the media ideology behind positive palm oil reporting. The research method uses a qualitative approach by analyzing the news content of local media Borneonews in Central Kalimantan Province with the specific issue of palm oil news as primary data. This research also uses secondary data obtained from various documents. The research results show that the local media Borneonews has the same tendency to commodify content in reporting on palm oil issues. The content is part of propaganda that leads public opinion to make peace with the presence of palm oil. The perspective disseminated through news content is that oil palm provides employment land for the community and care for the environment by processing palm oil waste so that it can be used for various other purposes such as animal feed and fertilizer. The ideology of the local media Borneonews in environmental issues with positive issues is that the messages conveyed are a denial of the existence of palm oil, not as a destroyer of the environment